Semitransparent Perovskite Solar Cells: From Materials and Devices to Applications - Shi, Biao; Duan, Linrui; Zhao, Ying; Luo, Jingshan; Zhang, Xiaodan (Advanced materials (Weinheim), 2020)
Semitransparent solar cells (ST‐SCs) have received great attention due to their promising application in many areas, such as building integrated photovoltaics (BIPVs), tandem devices, and wearable electronics. In the past decade, perovskite solar cells (PSCs) have revolutionized the field of photovoltaics (PVs) with their high efficiencies and facile preparation processes. Due to their large absorption coefficient and bandgap tunability, perovskites offer new opportunities to ST‐SCs. Here, a general overview is provided on the recent advances in ST‐PSCs from materials and devices to applications and some personal perspectives on the future development of ST‐PSCs. Semi‐transparent perovskite solar cells (ST‐PSCs) have received great attention due to their promising applications in many areas, such as building integrated photovoltaics (BIPV), tandem devices, and wearable electronics. A general overview of recent advances in ST‐PSCs from materials and devices to applications is provided, and presented alongside some personal perspectives on their future development.